CORRIGENDUM: Georgieva E, Yancheva V, Velcheva I, Becheva M, Stoyanova S. Histological alterations under metal exposure in gills of European perch (Perca fluviatilis L.) from Topolnitsa Reservoir (Bulgaria). Arch Biol Sci. 2015;67(2):729-737 - Team, Editorial (Archives of Biological Sciences, 2018)
https://doi.org/10.2298/ABS1801215E The corresponding author of the article Georgieva E, Yancheva V, Velcheva I, Becheva M, Stoyanova S. Histological alterations under metal exposure in gills of European perch (Perca fluviatilis L.) from Topolnitsa Reservoir (Bulgaria). Arch Biol Sci. 2015;67(2):729-737 has requested to change the affiliations of author Maria Becheva. The affiliations of author Maria Becheva are as follows: Maria Becheva Medical College, Medical University of Plovdiv, Plovdiv, Bulgaria Link to the corrected article: https://doi.org/10.2298/ABS141020034G